2015
DOI: 10.1302/0301-620x.97b1.33924
|View full text |Cite
|
Sign up to set email alerts
|

Does amputation offer any survival benefit over limb salvage in osteosarcoma patients with poor chemonecrosis and close margins?

Abstract: A poor response to chemotherapy (≤ 90% necrosis) for osteosarcomas leads to poorer survival and an increased risk of local recurrence, particularly if there is a close margin of excision. We evaluated whether amputation confers any survival benefit over limb salvage surgery (LSS) with narrow margins in patients who respond poorly to chemotherapy. We only analysed patients with an osteosarcoma of the limb, a poor response to chemotherapy and close margins on LSS (marginal/intralesional) or primary amputation: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 31 publications
7
67
1
2
Order By: Relevance
“…In large two metaanalyses involving more than 1,300 patients, our observations were confirmed where also a worse prognosis was found in patients who underwent amputation [10][11][12]. However, He et al presented different data in his meta-analysis, in which he did not find a statistically significant difference in the 5-year OS and the incidence of local recurrence in patients treated with a salvaging procedure and amputation [13].…”
Section: Discussionsupporting
confidence: 72%
“…In large two metaanalyses involving more than 1,300 patients, our observations were confirmed where also a worse prognosis was found in patients who underwent amputation [10][11][12]. However, He et al presented different data in his meta-analysis, in which he did not find a statistically significant difference in the 5-year OS and the incidence of local recurrence in patients treated with a salvaging procedure and amputation [13].…”
Section: Discussionsupporting
confidence: 72%
“…Published research shows that patients undergoing such treatment are characterized by a better total survival rate as compared with patients after amputation, not to mention reducing physical disability and its psychological effects that occur in patients undergoing such mutilating procedure [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, although mice in the FGR with rVSV‐K group tended to survive for a longer period than those in the NGR groups, there were no significant differences statistically, and distant metastasis occurred in all groups. Reddy et al reported that no difference was observed in survival outcome between limb salvage surgery with local recurrence and initial amputation without local recurrence . Whether local recurrence correlates with survival outcome in osteosarcoma patients is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence after adjuvant therapy is most resistant to treatment . Moreover, it is unclear whether local recurrence affects overall survival in addition to affecting adjuvant chemotherapy . Thus, it should be considered in the outcome of the surgical management of osteosarcoma.…”
mentioning
confidence: 99%